Prereading Activities for Content Area Reading and Learning - Readence, John E.; Moore, David W.; Rickelman, Robert J. (International Reading Association, 2004)
Research has informed educators about the value of preparing students for reading in the content areas, but how do teachers begin the complicated task of planning effective prereading activities that maximize their students' learning? This book provides practical activities that promote the learning of adolescents in their daily work in content classrooms. This third edition of the book differs from the second edition in two significant ways. First, it contains updated material that reflects the most recent information that has been revealed about prereading activities, and second, it concludes with a new chapter that addresses the nuances of selecting, combining, and using prereading activities across lessons and units. Other chapters offer valuable strategies for asking and answering questions before reading, forecasting passages, understanding vocabulary, graphically representing information, and writing before reading. The wealth of strategies and the expanded reference list offered in the book will help teachers make printed materials in all content areas understandable and interesting to students. (NKA)